PI-based ZSVM Control of Quasi-Z-Source Inverter for Photovoltaic Applications in Standalone Mode - Essaid Jaoide; Faicel El Aamri; Mbarek Outazkrit; Abdelhadi Radouane; Azeddine Mouhsen (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
The power converters Z-source topology are becoming a promoter solution for the energy conversion. This topology has the ability to boost and convert the voltage in a single-stage, unlike the famous two-stage conventionnel structure. The Quasi-Z-Source Inverter (QZSI) is nowadays the subject of several research works. However, it is the most suitable for PV applications, due to his continuous input current, which allows to harvest the maximum power available from the PV panels. In this regard, this paper investigates the dynamic characteristics of the QZSI through the small signal analysis, as well as the scheme control with the SVPWM technique for QZSI in standalone mode. The simulation results illustrate the practicability and the validity of the control scheme proposed.